SOURCES OF THE LATE MESOZOIC CARBONATITES OF WESTERN TRANSBAIKALIA: TRACE-ELEMENT AND SR-ND ISOTOPIC DATA - Yarmolyuk V.V.; Nikiforov A.V.; Kovalenko V.I.; Ivanov V.G.; Zhuravlev D.Z. (My University, 2001)
Carbonatites of the western Transbaikalia rift zone were formed in the middle of the Early Cretaceous (130-120 Ma) and are represented by lavas, tuffs, dikes, and veins. They are associated with other highly alkaline magmatic rocks (tephrites, phonolites, shonkinites, and nepheline syenites). Alkaline silicate rocks and carbonatites of these carbonatite associations have common trace-element features. The silicate rocks are richer in Sr, Ba, Pb, REE (particularly, LREE) and much poorer in Rb, Nb, Ta, Zr, and Hf than the oceanic island basalts (OIB). The anomalies of these elements are much stronger in the carbonatites, which contain a few percent of Sr, Ba, and REE and include specifie mineralization with baritocelestine, barite, strontianite, bastnaesite, and parisite. Sr and Nd isotopic compositions of the studied rocks vary from ε Nd = -1.6 and ε Sr = +11.8 in associations dominated by silicate rocks to ε Nd=-6.4 and ε Sr = +22 in associations almost solely composed of carbonatites. These variations are probably related to the contribution to the magma compositions from two isotopically distinct sources, which we call as "tephritic" and "carbonatitic." The proposed genetic model for the carbonatite associations suggests the melting of a "tephritic" mantle, which was metasomatized by a carbonate fluid with isotopic characteristics of the "carbonatitic" source. These metasomatic events caused the formation of carbonates in the mantle source. The melting of this source produced carbonatite melts.
Keywords: Mesozoic; Carbonatites; Transbaikalia; Mesozoic; Мезозой